THE INFLUENCE OF HYPNOSIS LEARNING STRATEGIES AND MOTIVATION ON READING COMPREHENSION OF FIFTH-GRADE STUDENTS - Junianengrum Junianengrum; Rufii Rufii; Retno Danu Rusmawati (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2020)
The purposes of this research were to discover: (1) the difference in the ability of reading comprehension of the fifth students who received Hypnosis Learning and of the students who were no, (2) the difference reading comprehension of the students who have high and low motivation, (3) the interaction between the application of hypnosis learning students’ motivation against their reading comprehension. This experimental research was carried out using simple random sampling. The subjects of research were grade 5 students of SDN Tropodo 2 and SDN Waru I of Sidoarjo Regency in the school year of 2017/2018 consisting of five classes of 187 students. There were four classes as the research subjects; two classes as the experimental and two classes for the control groups. The total number was 147 students. The research hypothesis was tested using ANOVA.The results of this research indicated that: (1) there was a significant difference in reading comprehension of fifth-grade students who got Hypnosis Learning and those who did not (F-value =130.203, with sig.=0.000). From the average score in the reading comprehension, the students who got Hypnosis Learning had an average score of 86.4444 higher than students who did not.(79.00), (2) there was a significant difference in reading comprehension of the students who had high motivation of learning and the students with low one (F-value = 26.426, with sig. = 0.000), (3) there was an interaction between the application of hypnosis learning and motivation towards the students’ reading comprehension, with F-value of 4.011 and significance level of 0.047.